Increased Rho kinase activity in patients with heart ischemia/reperfusion - Zhang, Juan; Xu, Fei; Liu, Xiao-Bo; Bi, Shao-Jie; Lu, Qing-Hua (Perfusion, 2019)
Rho kinase is a downstream effector of Rho GTPase that is known to regulate various pathological processes. The aim of this study was to evaluate the regulation of Rho kinase activity in leukocytes in patients with ischemia/reperfusion (I/R) injury. We investigated 38 patients with acute ST-segment elevation myocardial infarction (STEMI), 26 patients with atherosclerosis (AS) and 22 normal subjects. All patients underwent coronary angiography (CAG) and all STEMI patients received primary percutaneous coronary intervention (PPCI) of the left anterior descending artery (LAD) within 12 h after chest pain on-set. Blood samples for leukocyte Rho kinase activity were obtained before CAG and 3 and 24 hours after CAG/PCI. Rho kinase activity increased in the I/R and AS groups. Compared with the AS group, Rho kinase activity was significantly higher in peripheral blood leukocytes in STEMI/PPCI. Furthermore, there was no correlation between changes in Rho kinase activity and changes in high-sensitivity troponin I (hs-TnI) and C-reactive protein (CRP). There was a negative correlation between Rho kinase activity and IL-6. Rho kinase is involved in the pathogenesis of heart I/R injury in patients. Inhibition of Rho kinase may be an additional therapeutic intervention for the treatment of I/R.